Factors Related to Vulvovaginal Itching and Discharge Among Iraqi Women - Al-Najjar, Dunya H; Al-Ogaili , Zainab T.; Al-Jerrah , Israa H. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Vaginal infections are considered global health problems for women in child-bearing ages. At the time in which various pathogenic organisms are responsible for those infections, many risk factors may also be attributed for such infections, including sexual activity and partner, contraceptive use, personal hygiene level, female estrogen level and its effect on vaginal mucosa, medical history, and many other factors. However, the disease by itself is not considered an exclusive sexually transmitted infection. Objective: The goal of the Study is to identify the causes and factors related to the symptoms of vulvovaginal itching and/or vaginal discharge. Methodology: A cross sectional study conducted on 93 females (16 pregnant &77 non pregnants females) attending the private clinics in Al-Hindiya district (Karbala governorate) from May 2019 to September 2019. Ethically, patients’ information was treated with confidentiality and privacy throughout data collection and analysis. Tow swabs had been taken from each patient (vaginal and cervical) and sent to a private lab for direct microscopic examination and culturing on appropriate media. Statistically, the quantitative variables were analyzed using non-parametric t-test and the qualitative variables were analyzed using Chi-square test. Results: Fortunately, the age of all participants was within child-bearing age ranging 15 to 42 with a mean of 28.0 ± 6.9 years. There was no significant association of pregnancy with vaginal infections as noticed in this study, while diabetes mellitus (DM) was found to be significantly related to the presence of infection (P-value=0.003). Similarly, intrauterine contraceptive device (IUCD) usage was also found to be significantly related to the occurrence of infection (P-value = 0.040). On the other, the lab study showed that E. coli is the most common pathogen to be expected in women complaining of vulvovaginal itching and/or vaginal discharge with monilial being the second. Conclusions: DM and IUCD usage had their burdens on the vaginal cavity causing increasing rate of vaginal symptoms as proven significantly. Simultaneously, the cultivation results revealed that E. coli is the causative agent for of vulvovaginal itching and/or vaginal discharge at the level of our females, a point meriting further evaluation.